2010
DOI: 10.1111/j.1532-849x.2010.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreign-Trained Dentists in Advanced Education in Prosthodontics Programs in the United States: Demographics, Perspectives on Current Training, and Future Goals

Abstract: FTDs differed from USTDs in several ways. Because of their interests in academics and research, FTDs may potentially have a positive impact on the development of the prosthodontics discipline. This information may be beneficial for AEP program directors in accommodating the needs of FTDs, and for FTDs in better preparing for their AEP training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This study found that in all papers resulting from collaboration among multiple countries, an HI country was always involved in the publication. A significant proportion of residents in US graduate prosthodontic programs are graduates of dental schools outside the US 22,23 . It is possible that residents training in HI countries return to their native countries following graduation, maintaining professional ties with institutions where they studied to collaborate on projects.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that in all papers resulting from collaboration among multiple countries, an HI country was always involved in the publication. A significant proportion of residents in US graduate prosthodontic programs are graduates of dental schools outside the US 22,23 . It is possible that residents training in HI countries return to their native countries following graduation, maintaining professional ties with institutions where they studied to collaborate on projects.…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that higher tuition rates are necessary to pay for services that international students use exclusively or more intensively than others, such as the monitoring and reporting requirements to the federal government (F-1 and other non-immigrant visas, the Student and Exchange Visitor Information System (SEVIS)); and other services to a population of non-native English speakers, including the International Students and Scholar Office [ 27 ]. This same argument can be extrapolated to dentistry, where foreign trained dentists pay higher tuition than U.S. trained dentists [ 16 ]. For example, the projected tuition and fees for the 2-year international dentist program at University of Colorado for the class of 2019 is $157,260 USD ($78,630 USD each year); whereas, the yearly rates for Colorado residents and non-residents are $36,205 USD and $61,508 USD, respectively [ 28 ].…”
Section: Resultsmentioning
confidence: 97%
“…After title and abstract screening, 29 publications that did not answer the focused question or were duplicates were excluded. In total 18 articles were sought, including nine articles [ 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] discussing workforce diversity in dentistry ( Table 1 ); and nine articles [ 1 , 2 , 8 , 9 , 10 , 22 , 23 , 24 , 25 ] discussing licensing process for foreign-trained dentists ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Munoz et al reported that, for 1994 to 2002, there were fewer graduates of U.S. dental schools applying to AEPPS than international graduates 20 . Al‐Sowygh and Sukotjo reported that the number of foreign‐trained dentists enrolled in prosthodontic specialty programs was almost 50%, based on an ACP survey in 2002‐03 33 . Since then, there has been an increase in the interest of U.S. graduates in pursuing prosthodontic specialty training 32 .…”
Section: Discussionmentioning
confidence: 99%